How Different Preparation Techniques Affect MRI-Induced Anxiety of MRI Patients: A Preliminary Study - Hamd, Zuhal Y.; Alorainy, Amal I.; Alrujaee, Lena A.; Alshdayed, Maha Y.; Wdaani, Afrah M.; Alsubaie, Atheer S.; Binjardan, Layal A.; Kariri, Sarab S.; Alaskari, Rawan A.; Alsaeed, Marah M.; Alharbi, Mohammed Awad; Alotaibi, Marzouk Sari.; et al. (MDPI, 2023)
Background: Magnetic resonance imaging (MRI) exams may cause patients to feel anxious before or during the scan, which affects the scanning outcome and leads to motion artifacts. Adequate preparation can effectively alleviate patients’ anxiety before the scan. We aimed to assess the effect of different preparation methods on MRI-induced anxiety: We conducted a prospective randomized study on MRI patients between March and May 2022. We divided 30 patients into two groups: the control group, which received routine preparation (RP), and the experimental group, which received video preparation (VP).We used the State-Trait Anxiety Inventory (STAI) to measure anxiety levels before and after the interventions. We assessed patients’ self-satisfaction after the scan: After preparation, VP (STAI mean = 10.7500) and RP (STAI mean = 12.7857), we observed a significant association between the pre- and post-STAI results in VP (p = 0.025). The effects of both methods in decreasing anxiety were more significant for first-timers (p = 0.009 in RP/0.014 in VP). We noted high satisfaction levels for both forms of preparation. The VP technique was superior in reducing patient anxiety, especially in first-time MRI patients. Hence, VP techniques can be used in different clinical settings to reduce anxiety and facilitate patients’ understanding of the instructions given.